(untitled) (College of Basic Education Research Journal, 2025)
This study investigates metaphors in COVID-19- related English texts. The study shows an overview on how people are suffer from pandemic and its negative effects, it is not preferable to talk about COVID-19 always explicitly. Metaphorical expressions assist in conveying meaning successfully. They are essential in transferring message of text appropriately and successfully for they are capable of adding force to the meaning conveyed. Study utilized Conceptual Metaphor Theory by Lakoff and Jonson (1980) as a model to analyze chosen data. Conceptual Metaphor Theory has been adapted by adding frames and mind maps to simplify metaphorical project from source domain onto target domain. Data are selected from English social media like Twitter, Facebook, and other websites like medical websites , online articles and journals concerning pandemic expressions related to metaphors. Ten English COVID-19 metaphorical expressions have been chosen for analysis. It is found that virus has been used as an Abstract Target Domain. Also, it is found that Concrete Source Domains (Fire) and (war) are the most frequent ones and they occurred five times separately out of total number of data.